1998
DOI: 10.1136/jnnp.65.3.301
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of CNS impairment in HIV infection: clinical, neuropsychological, EEG, and MRI/MRS study

Abstract: Objectives-Toidentify by clinical examination, EEG, MRI, and proton spectroscopy, and neuropsychological assessment the prevalence of signs of CNS involvement in patients infected with HIV, and to relate such findings to the evidence of immunosuppression. Methods-The design was a cross sectional analysis of a cohort of male patients with infected HIV with an AIDS defining diagnosis or low CD4 count (<350), and seropositive asymptomatic subjects, both groups being followed up in a longitudinal study. Control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 40 publications
2
26
0
Order By: Relevance
“…Aylward et al (1995) showed that the white matter volume in demented AIDS patients was less than in those who were non-demented. Harrison et al (1998) found that patients who performed poorly on neurocognitive tests were more likely to have T2-hyperintense white matter abnormalities on MRI. Neither of these studies specified white matter regions associated with this neuropsychological impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Aylward et al (1995) showed that the white matter volume in demented AIDS patients was less than in those who were non-demented. Harrison et al (1998) found that patients who performed poorly on neurocognitive tests were more likely to have T2-hyperintense white matter abnormalities on MRI. Neither of these studies specified white matter regions associated with this neuropsychological impairment.…”
Section: Discussionmentioning
confidence: 99%
“…While the association between presence of WMHs and cognitive decline in the general population is well recognized, the relationship between WMHs and cognitive performance in individuals living with HIV infection is still somewhat controversial. WMHs have been reported to be associated with some cognitive measures, including worse performance on tests of psychomotor speed and verbal memory (34). Additionally, decreased white matter volume in HIV seropositive individuals has been associated with dementia (35).…”
Section: Discussionmentioning
confidence: 99%
“…These studies consistently revealed a severe reduction of NAA in the cortex and frontal white matter in those with more severe cognitive impairment [54][55][56][57][63][64][65][66][67][68]. Furthermore, increasing levels of Cho and mI in the basal ganglia and the frontal white matter were also associated with an increasing severity of cognitive impairment and a greater decline in CD4 count [12,54]. While these findings are fundamental to our understanding of the underlying metabolic mechanisms behind the progression of cognitive decay in patients with HIV dementia, more research is needed to determine how HIV affects those in the early disease stage as well as asymptomatic subjects.…”
Section: Magnetic Resonance Spectroscopymentioning
confidence: 99%
“…The most common findings included regional gray matter atrophy, particularly in the basal ganglia [4][5][6], Electronic supplementary material The online version of this article (doi:10.1007/s13311-010-0010-4) contains supplementary material, which is available to authorized users. white matter lesions [7,8], ventricular expansion [9], and global cerebral atrophy [7,[10][11][12]. More recent studies have further elucidated these effects using more advanced image acquisition and volumetric measurement techniques.…”
Section: Structural Magnetic Resonance Imagingmentioning
confidence: 99%
See 1 more Smart Citation